Elfin butterflies of the genus Rhamma Johnson (Lepidoptera: Lycaenidae: Theclinae): A review of the Colombian species - Prieto, Carlos; Vargas, Maria A. (Zootaxa, 2016)
The Colombian species of the genus Rhamma Johnson, 1992 are revised. Male and female phenotypes of all species are associated and diagnosed, and data on their distributions are given along with a discussion of the geographic variability of the species. Thirteen taxa are considered valid at the species level. The following taxonomic changes are proposed: Rhamma andradei (Le Crom & Johnson), stat. nov, comb. nov.; previously considered a nomen dubium in Penaincisalia Johnson, the taxon is considered a valid species of Rhamma. The placement of Rhamma anosma (Draudt), comb. nov., described as Thecla, is confirmed as belonging to Rhamma. A lectotype is designated for Thecla mishma Hewitson, 1878. Adults, male and female genitalia, and distribution maps are depicted for all species, along with an identification key based on adults.